Attestation audits revisited : how about performance audits for public companies? / Haji Shafi Mohamad - Mohamad, Shafi (Universiti Teknologi MARA, Sarawak, 2004)
The primary objective of this paper is to study the possibility of making performance audits mandatory initially at least for all publicly-listed companies. Auditing the performance of management and commenting on how economically, efficiently and effectively they have performed their duties is not a new subject. However, up until now the results of performance audits have usually been kept within the organization concerned ('in-house'). With the growth of perceived dissatisfaction with current auditing practices and the demand for more management accountability due to corporate collapses, this paper considers the possibility of performance audits being made mandatory. Problems to be overcome in establishing a performance audit framework include audit independence, cost/benefit decisions and the establishment of adequate measurement criteria. However, if the demands for performance audits escalate these problems will have to be overcome. Indeed they are not now seen as insurmountable. If the general public and the business community consider that this is the function they want an audit to perform in the future, for all entities both public and private, then performance auditing may acquire just as important a status as currently held by financial statements auditing. Therefore debate over the potential benefits of compulsory performance audits continues to increase.